SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KARYAWAN BERPRESTASI DENGAN METODE SIMPLE ADDITIVE WEIGHTING PADA PT FORTECH INDOTAMA - Tri Agus Setiawan; Nurmalasari Nurmalasari; Dwi Yuni Utami (STIKOM CKI, 2018)
In a company or organization outstanding employee appraisal is very important in order to motivate employees in the work, evaluating and planning the future. Outstanding employee assessment should be done with a good and appropriate methods, so as to produce a correct judgment. In determining the top performers with a subjective assessment is less precise because of the absence of assigning weights to each criterion in the assessment that may not pay attention to aspects of another assessment. Then the decision support system can be used to assess top performers with Simple Additive weighting method (SAW). Simple Additive weighting method chosen for assessing and ranking the performance keryawan. From the test results it can be concluded that this application can be used for the assessment of outstanding employee at PT.Fortech Indotama.